Compositional evidence of magmatic activity on Vesta. Issue 9 (2nd May 2014) - De Sanctis, M. C.; Ammannito, E.; Buczkowski, D.; Raymond, C. A.; Jaumann, R.; Mittlefehldt, D. W.; Capaccioni, F.; Capria, M. T.; Frigeri, A.; Magni, G.; Tosi, F.; Zambon, F.; et al.
Abstract Like the Earth and other terrestrial planets, the asteroid Vesta has a basaltic crust and a large iron core; its surface is dominated by impact craters of all sizes and has tectonic features. The presence of basaltic compositions, olivine, howardite‐eucrite‐diogenite meteorites, and models of Vesta's formation, suggests that volcanic and/or magmatic activity could have occurred on Vesta. A global search for lobate structures did not find unequivocal evidence of volcanic features. Nevertheless, several morphological properties of Brumalia Tholus on Vestalia Terra suggest that this topographic high most likely formed as a magmatic intrusion. The presence of more orthopyroxene‐rich material relative to surrounding terrain in the ejecta of Teia, a fresh impact crater on the northern face of Brumalia Tholus, supports the hypothesis of magmatic intrusions on Vesta.